The Role of 18F-FDG PET/CT in staging of gallbladder carcinomas - Arslan, Esra; Aksoy, Tamer; Dursun, Nevra; Gürsu, Rıza Umar; Sevinç, Mert Mahsuni; Çermik, Tevfik Fikret (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Gallbladder Carcinoma (GBC) is the most common and aggressive tumor of the biliary tract. Patients are typically diagnosed during advanced stages, and the mean overall survival is short. In our study, we aimed to demonstrate the uptake patterns of 18F-FDG PET/CT in GBC, as well as its association with survival and diagnostic value during the initial stage. Materials and Methods: Overall, 17 patients with GBC were retrospectively included in the study. 18F-FDG PET/CT study was performed for pretreatment staging. Two different standardized uptake values (SUVmax and SUVmean), metabolic tumor volume 40% (MTV40), and tumor lesion glycolysis (TLG) of the primary tumors were compared between the clinical and histopathological groups. Results: Of the 17 patients, 11 were women (64.7%), and 6 (35.3%) were men. The mean age of the patients was 69.7±8.8 years. 18F-FDG uptake was detected in all lesions. Mean SUVmax was calculated to be 15.4±13.7 (median=10.6, range=3.4-46.8). All distant metastases (52.9%) were detected in the liver. Semiquantitative metabolic parameters (SUVmax and SUVmean, MTV40, and TLG) obtained from patients with distant metastasis were not significantly higher than those without distant metastasis. Similar results were obtained in patients with and without nodal metastasis. No statistically significant intergroup difference was observed regarding metabolic parameters. However, a statistically significant negative correlation was observed between the patient’s age and the SUVmax of the primary lesion and metastatic lymph nodes (r=−0.564, p=0.018). During 10.7±10.4 months of mean follow-up, the mean survival of patients with distant metastases (6.1±11.0 months) was significantly shorter than that of patients with no organ metastases (15.8±7.1 months). Conclusion: In our study, distant metastases and age were observed to be crucial prognostic factors in patients with gallbladder carcinoma (GBC). In addition, we believe that 18F-FDG PET/CT imaging will help to stage the GBC, detect nodal and distant metastasis, and evaluate the metabolic state of gallbladder lesions.